Investigating Consumer Demand and Willingness to Pay for Fresh, Local, Organic, and “On-the-Stalk” Edamame - Lord, Nick; Zhang, Bo; Neill, Clinton L. (Frontiers in Sustainable Food Systems, 2021)
Introduction of locally adapted, commercially viable edamame varieties can allow it to be marketed as fresh, local, organic, or on the stalk. Here, we utilized a one-and-one-half bounded (OOHB) elicitation format to estimate mean willingness to pay (WTP) for these external attributes in relation to a vector of explanatory variables. Results showed 84-, 85-, and 28-cent premiums for fresh, local, and organic edamame (10 oz). Pro-environmental attitudes drove WTP for all three of these attributes, while shopping location significantly increased mean WTP for fresh and organic attributes. A 40-cent price discount was observed for the “on-the-stalk” attribute, suggesting that convenience also plays an important role in marketing edamame. The results suggest that more research regarding edamame demand is warranted.